Optimalisasi Kinerja Akademik Melalui Efikasi Diri, Motivasi Akademik dan Sumber Daya Teknologi Informasi dan Komunikasi - Eli Masnawati; Yulius Kurniawan; M Sukron Djazilan; Mila Hariani; Didit Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The research described in this study aims to evaluate the extent to which academic performance is influenced by self-efficacy, academic motivation, and information and communication technology resources. This study involved a quantitative design using multiple linear regression analysis tools. The target population is 120 students who are carrying out their studies in the city of Surabaya. The sampling technique is purposive sampling. The research results show that there is a significant positive relationship between self-efficacy and student academic performance. Students who have a high level of self-efficacy tend to achieve better academic achievements. Apart from that, academic motivation also has a strong influence on academic performance. Motivated students can achieve their academic goals and tend to achieve higher results. Information and communication technology resources were also found to have a significant impact on academic performance. Students who have access to and use information and communication technology in their learning process have greater opportunities to achieve higher academic achievements